The voices of community pharmacists during the COVID-19 pandemic in Puerto Rico - Silva-Suárez, Georgina (J Am Pharm Assoc (2003), 2022)
BACKGROUND: Community pharmacists have provided health care services uninterruptedly throughout the coronavirus disease 2019 (COVID-19) pandemic. However, their public health role is often overlooked. OBJECTIVES: The purpose of this article is to discuss the roles and the coping mechanisms of community pharmacists working during the COVID-19 pandemic in Puerto Rico. METHODS: A cross-sectional study, using an electronic survey, was conducted to assess the community pharmacists’ response during the COVID-19 pandemic in Puerto Rico. Two open-ended questions explored community pharmacists’ opinions about the pharmacist’s role and coping mechanisms during the pandemic. The responses were analyzed following an inductive thematic analysis. Two major themes emerged from their responses: professional and personal experiences. RESULTS: Of the 302 participants who completed the survey, 77% of them answered 1 or both open-ended questions. The answers were diverse, and the respondents went beyond the specific topics asked. In professional experiences, important roles as educators and providing continuity of care and emotional support to their patients were highlighted. They also expressed concerns and frustrations on the profession’s shortcomings, feeling overworked yet with a lack of recognition. In personal experiences, most of the respondents were concerned about the impact of having to juggle work and home life. They also reported mental health concerns, expressing feeling stressed, overworked, and worried about the constant risk of exposure and fear of exposing their loved ones. CONCLUSION: Community pharmacists in Puerto Rico ensured the continuation of care, provided education, and managed anxious and stressed patients. Most relied on family members to cope with the extra burden that the COVID-19 pandemic. The lack of recognition created resentfulness among participants. It is essential to listen to our community pharmacists’ voices to support and respond to their needs and learn from their experiences as frontline health care workers.